Convergence of urban and environmental research elds in conceptual proposals towards urban sustainability: improvement and challenges - Tão, Nícolas Guerra Rodrigues; Faustino, Alexandre da Silva; da Silva, Ricardo Siloto; Peres, Renata Bovo (Revista Thésis, 2017)
Currently, there are new theoretical approaches that mix concepts of both environmental and urban sciences. This search for inter- disciplinarity aims the development of guidelines to respond more holistically the demands of the population. These guidelines should be based on the various dimensions assigned to sustainable de- velopment. In this sense, what perspective can be established on urban planning that enables it to contribute for the environmental quality of cities and hence for the quality of human life? How some disciplines and theories that re ect on the processes and natural ows can bring alternatives to the urban setting that reduce the clearance of environmental and urban dimensions? In these terms, this article proposes the critical analysis of the concepts of urban ecology and biophilic cities, and concepts of sustainable urbanism and ecological urbanism as proposals that question environmental issues in urban setting, and vice versa. Parallels between models are established. Possible challenges and opportunities for the in- tegration of social and environmental dimensions of sustainability in the context of urban space are discussed. In addition, some implications for urban projects are placed. Thereunto, this study conducted an exploratory and descriptive research, in theoret- ical-conceptual nature, with typology of bibliographical technical procedure. The product of this process is the critical analysis of a comparative matrix, which contains the main in uences, concepts, strategies, implications for urban projects, approximations to sus- tainability and challenges of the surveyed approaches. It was evi- dent that they alone are not able to ll the wide range of problems facing the urban space; each of which has varying levels of in- volvement with the di erent pillars of sustainability. Alternatively, it is possible to think locally in a better ownership of its principles and strategies. The tactics tend to be more assertive if arising from the dialogue between concepts